Préservation de l’orientation et convergence de Newton-Raphson avec le modèle hyperélastique compressible de Blatz-Ko - Peyraut, François; Labed, Nadia (European Journal of Computational Mechanics, 2001)
This paper deals with the Blatz-Ko hyperelastic compressible model in the case of a cubic structure under compression loading by a press. With some particular increment loading values, we show that the orientation is not preserved. In this case, the incremental Newton-Raphson algorithm diverges. With the arc length method, we obtain a similar conclusion for some arc length values. So we suggest to control the convergence by using optimal numerical parameters. These optimal numerical parameters guarantee the orientation preservation and a minimal time computation.